Welfare effects of nudges: The emotional tax of calorie menu labeling - Thunstrom, Linda (Judgment and decision making, 2019)
Traditionally, information has been assumed to never harm consumers, a notion recently challenged. Salience nudges have been argued to evoke negative emotions, therefore acting as “emotional taxes”. I design a hypothetical restaurant meal experiment to analyze the emotional and short-term consumer welfare impact of a calorie salience nudge (calorie menu labeling) – a policy implemented nationwide in the U.S. in 2018. I find that a calorie salience nudge may act as an emotional tax, but only for some – there is considerable heterogeneity in the emotional response to the nudge. In particular, the nudge emotionally taxes people with low eating self-control, while it emotionally subsidizes those with higher levels of eating self-control. It therefore emotionally taxes the “right” people. However, people with lower levels of self-control may experience fewer benefits from the nudge – the nudge causes them to adjust their high calorie meal consumption by less than do those with higher self-control. It is therefore unsurprising that consumers with lower self-control attach a lower (a negative) value to the calorie salience nudge. Overall, the calorie salience nudge positively affects consumer welfare, although heterogeneity over consumers is substantial – the consumer value ranges from positive to negative. I find no distributional effects over income from the calorie salience nudge.